Ivabradine in Heart Failure with Reduced Ejection Fraction (HFrEF): A Narrative Review of Clinical Outcomes - Hidayaturahmah, Rizky; Khoerunisa, Erin; Suprahman, Nisa Yulianti; Novitasari, Fia (Faculty of Pharmacy, Universitas Gadjah Mada, 2026)
Background: Therapy for heart failure with reduced ejection fraction (HFrEF) patients is complex, involving several combinations of treatments, but there are still some problems, such as rehospitalization, reduced ejection fraction values, increased heart rate, and decreased quality of life. Ivabradine, a selective heart rate-lowering agent, offers adjunctive therapeutic benefits.Objective: This study aims to determine the characteristics of HFrEF patients who received additional therapy with ivabradine and to determine how ivabradine affects their clinical outcomes.Methods: This narrative review searched articles on PubMed, Cochrane Library, Google Scholar, and ScienceDirect. The research was limited to randomized controlled trial articles, observational studies, and cohorts with international and national English and/or Indonesian articles published in the last 10 years.Results: Twenty-eight studies (n=36,765) met the problem formulation and inclusion criteria were analyzed. Patients receiving ivabradine were predominantly male (74.9%), aged 56-65 years (81.9%), and had a history of smoking. Most patients had heart rate ≥70 bpm (75.4%), LVEF ≤30% (55.3%), BMI ≥28 kg/m² (87.1%), and NYHA class II-III (85.5%). The addition of ivabradine to the clinical outcome of HFrEF patients reduces heart rate (15.7 bpm), blood pressure (SBP: -4.4 mmHg; DBP: -0.9 mmHg), rehospitalization, and mortality, while improving LVEF and stroke volume, and quality of life. Adverse effects included manageable bradycardia and transient visual disturbances.Conclusion: Ivabradine effectively improves clinical outcomes in HFrEF patients as adjunct therapy, with significant benefits in cardiac function, symptom control, and prognosis.